Tapak Perlekatan Reseptor Virus Flu Burung yang Diisolasi dari Berbagai Unggas Sejak tahun 2003 sampai 2008 (RECEPTOR BINDING SITE OF AVIAN INFLUENZA VIRUS H5N1 ISOLATED FROM VARIOUS POULTRIES SINCE 2003 TO 2008) - Wibowo, Michael Haryadi; Tabbu, Charles Rangga; Asmara, Widya; Susetya, Heru (Jurnal Veteriner; Vol 13 No 2 (2012), 2013)
Avian Influenza (AI) is an infectious disease in poultry, caused by type A of avian influenza virus(AIV), in the family of Orthomyxoviridae. Almost all birds’ species are sensitive to the AI. Beside theability to infect various species of poultry. AIV type A has a wide range of host including all bird species,mammals, dan human. Today some scientists reported that the cases of AI in mammals, including humansare increasing. This condition suggests that the AI virus circulated in the field may have some mutationsin the amino acid determinants responsible receptor binding site (RBS). A research was therefore designedto investigate the molecular level of HA gen fragment responsible for receptor binding site of AIV isolatedfrom various poultry since 2003 to 2008. Molecular characterization was based on the amplification ofreceptor binding site of HA gene by reverse transcriptase polymerase chain reaction (RT-PCR). All RTPCRof HA gene positive products were sequenced to determine the nucleotide composition at the targetedfragment. Sequences yielded were analyzed by program Mega 4.0 versions, including multiple alignment,deductive amino acid prediction, and establishment of phylogenetic tree. The results show that all AIVisolates could be determined of some conserved amino acids residues responsible for RBS which indicatethe binding preference of avian like receptor, sialic acid ? 2, 3 galactose except isolate A/Layer/Jabar/MHW-RBS-02/2008 which could be found a deletion of amino acid at position of 129 dan mutation of 151isoleucine into threonine. Phylogenetic study showed that clustering of AIV did not base on species of birdor geographic origin of AI viruses which were studied.
Keywords: avian influenza, haemagglutinin, amino acid, receptor binding site